2006
DOI: 10.1254/jphs.fp0060526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of d-Pseudoephedrine on Cough Reflex and Its Mode of Action in Guinea Pigs

Abstract: Abstract. d-Pseudoephedrine (PSE) is one of the main ingredients of Ephedrae herba. Although PSE is widely applied for patients with a common cold and upper respiratory inflammation as a decongestant, the effects of PSE on cough have never been reported. In this study, we investigated the antitussive effects of intraperitoneal injection of PSE on the cough reflex induced by microinjection of citric acid into the larynx of guinea pigs. PSE decreased the number of cough reflexes dose-dependently (−18.3 ± 5.0% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
11
0
3
Order By: Relevance
“…Further investigation of the regulatory mechanism on formation of these two compounds is ongoing. PEph was reported to have effect of anti-tussive, anti-inflammation and other effects, 4,26) suggesting the usefulness of Mongolian Ephedra plants to relieve rhinitis and nasal congestion.…”
Section: Ephedra Sinicamentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation of the regulatory mechanism on formation of these two compounds is ongoing. PEph was reported to have effect of anti-tussive, anti-inflammation and other effects, 4,26) suggesting the usefulness of Mongolian Ephedra plants to relieve rhinitis and nasal congestion.…”
Section: Ephedra Sinicamentioning
confidence: 99%
“…2) Pharmacological studies revealed central nervous system (CNS) stimulation, anti-tussive, decongestion, anti-inflammatory activities of ephedrine and its analogue, [3][4][5][6] providing the scientific basis underlying its traditional uses. Besides traditional usage in Asia, it has also been used as a dietary supplement in U.S.A. and Europe in recent years.…”
mentioning
confidence: 99%
“…Nos trabalhos experimentais a tosse pode ser provocada pela microestimulação elétrica direta do núcleo do trato solitário após descerebração (26), ou por estimulação mecânica/elétrica da mucosa das vias aéreas em animais conscientes ou sob anestesia geral.…”
Section: Métodos De Estudo Da Tosseunclassified
“…Entretanto, a naloxona, antagonista desses receptores, não impede a ação antitussígena da codeína no gato (14). É possível, então, que os narcóticos atuem também em receptores nãoopioides -talvez de glutamato, serotonina ou nociceptina -no SNC (17,26).…”
Section: Antitussígenos De Ação Centralunclassified
See 1 more Smart Citation